B Epitope Multiplicity and B/T Epitope Orientation Influence Immunogenicity of Foot-and-Mouth Disease Peptide Vaccines. (3rd December 2013) - Blanco, Esther; Cubillos, Carolina; Moreno, Noelia; Bárcena, Juan; de la Torre, Beatriz G.; Andreu, David; Sobrino, Francisco
Abstract : Synthetic peptides incorporating protective B- and T-cell epitopes are candidates for new safer foot-and-mouth disease (FMD) vaccines. We have reported that dendrimeric peptides including four copies of a B-cell epitope (VP1 136 to 154) linked to a T-cell epitope (3A 21 to 35) of FMD virus (FMDV) elicit potent B- and T-cell specific responses and confer protection to viral challenge, while juxtaposition of these epitopes in a linear peptide induces less efficient responses. To assess the relevance of B-cell epitope multivalency, dendrimers bearing two (B2 T) or four (B4 T) copies of the B-cell epitope from type O FMDV (a widespread circulating serotype) were tested in CD1 mice and showed that multivalency is advantageous over simple B-T-epitope juxtaposition, resulting in efficient induction of neutralizing antibodies and optimal release of IFN γ . Interestingly, the bivalent B2 T construction elicited similar or even better B- and T-cell specific responses than tetravalent B4 T. In addition, the presence of the T-cell epitope and its orientation were shown to be critical for the immunogenicity of the linear juxtaposed monovalent peptides analyzed in parallel. Taken together, our results provide useful insights for a more accurate design of FMD subunit vaccines.